Investigation of Nrf2, AhR and ATF4 Activation in Toxicogenomic Databases - Zgheib, Elias; Limonciel, Alice; Jiang, Xiaoqi; Wilmes, Anja; Wink, Steven; van de Water, Bob; Kopp-Schneider, Annette; Bois, Frederic Y.; Jennings, Paul (Frontiers in Genetics, 2018)
Toxicological responses to chemical insult are largely regulated by transcriptionally activated pathways that may be independent, correlated and partially or fully overlapping. Investigating the dynamics of the interactions between stress responsive transcription factors like Nrf2 (Nuclear Factor (Erythroid-derived 2)-Like 2), AhR (Aryl Hydrocarbon Receptor) and ATF4 (Activating Transcription Factor 4) from transcriptomic and toxicogenomic data and defining the signature of each of them is an additional step towards a system level understanding of perturbation driven mechanisms. To this end, we investigated the segregation of the genes belonging to the three following transcriptionally regulated pathways: the AhR pathway, the Nrf2 pathway and the ATF4 pathway. Toxicogenomic datasets from three projects (carcinoGENOMICS, Predict-IV and TG-GATEs) obtained in various experimental conditions (in human and rat in vitro liver and kidney models and rat in vivo, with bolus administration and with repeated doses) were combined and consolidated where overlaps between datasets existed. A bioinformatic analysis was performed to refine pathways’ signatures and then classify chemicals by their potency and selectivity of activation of each pathway. The obtained signatures confirmed the a priori information found in literature for the typically activated genes (e.g. CYP1A1 in AhR, SRXN1 in Nrf2 and HERPUD1 in ATF4), but also revealed recurrently inhibited genes for each pathway. Overlapping gene sets showed that the connection is very strong between AhR and Nrf2, and between Nrf2 and ATF4, but less between AhR and ATF4 that seem quite independent. Pathway signatures were stratified based on categories of experimental conditions to study the influence of species, model system, exposure time and exposure regime on the genes leading the signature. Example pathway activators available from the datasets were used to curate gene lists and rank other chemicals to test the quality of the gene signatures.